Effects of the dietary zinc source and vitamin E level on live weight and carcass yield and meat quality in male broilers reared under chronic cyclic heat stress conditions in the finisher phase - De Grande, Annatachja; Ducatelle, Richard; Leleu, Saskia; Rapp, Christof; Torres, Cibele; Petracci, Massimiliano; De Smet, Stefaan; Michiels, Joris; Haesebrouck, Freddy; Van Immerseel, Filip; Delezie, Evelyne (Frontiers in Physiology, 2022)
The objective of this study was to evaluate the effect of the interaction of zinc source (ZnSO4 vs. zinc amino acid complex) and vitamin E level (50 IU/kg vs. 100 IU/kg) on meat yield and quality in broilers subjected to chronic cyclic heat stress in the finisher phase. A total of 1224 day-old male Ross 308 broilers were randomly distributed among four dietary treatments. Each treatment contained nine replicates of 34 birds, housed in floor pens in a temperature and lighting controlled room. Treatments were organized in a 2x2 factorial arrangement: two sources of zinc, 60 mg/kg of Zn as ZnSO4 or 60 mg/kg of Zn as zinc amino acid complexes (ZnAA), combined with two levels of vitamin E (50 or 100 IU/kg). From day 28 until day 37 (finisher phase), all birds were subjected to chronic cyclic heat stress (32°C ± 2°C for 6h daily). In the present study, it was observed that replacing ZnSO4 by ZnAA, increased breast meat weight and yield of broilers reared under chronic cyclic heat stress conditions, whereas total slaughter yield was not affected. Moreover, it was observed that replacing ZnSO4 by ZnAA, resulted in breast meat with a lower drip and thawing loss and a higher marinade uptake. In conclusion, replacing ZnSO4 with more readily available ZnAA, can improve breast meat yield and increase water holding capacity of breast meat of broilers exposed to chronic cyclic heat stress at the end of the production cycle. However, as no thermoneutral group was included in the present study, the observed effects of zinc source cannot be generalized as a solution for heat stress. Moreover, the beneficial effects of ZnAA on breast meat yield and quality seem to be independent of the vitamin E level, and increasing vitamin E level has no additional beneficial effects.